Incidence of vascular brain damage in a population with Parkinson Disease: a clinical statistic study in comparison with a control group of patients afferent to neurological movement disorder outpatients clinic - Zarola, Flora (Acta Biomedica Atenei Parmensis, 2017)
N/A